Comparative analysis of clinicopathological correlations of cyclooxygenase-2 expression in resectable pancreatic cancer - Hermanova, Marketa; Karasek, Petr; Tomasek, Jiri; Lenz, Jiri; Jarkovsky, Jiri; Dite, Petr (World journal of gastroenterology, 2010)
AIM: To perform a comparative analysis of clinicopathological correlations of cyclooxygenase-2 (COX-2) expression in pancreatic cancer, examined by monoclonal and polyclonal antibodies. METHODS: The COX-2 expression in 85 resection specimens of pancreatic ductal adenocarcinoma was immunohistochemically examined using both monoclonal and polyclonal antibodies. The final immunoscores were obtained by multiplying the percentage of positive cells with the numeric score reflecting the staining intensity. COX-2 expression levels were classified into three categories (0, 1+, and 2+) and the clinicopathological correlations were statistically evaluated and analyzed. RESULTS: The positive tumor expression rates of COX-2 were 80.5% using monoclonal antibody and 69.4% using polyclonal antibody. In the Kaplan-Meier analysis, no significant correlations were found between levels of COX-2 expression and overall survival (OS), but trends to longer OS were found in COX-2 negative cases using monoclonal antibody. Significantly longer disease free survival was revealed in COX-2 negative cases using monoclonal antibody (P = 0.019). No correlations between COX-2 expression levels and grade (G), tumor (T) status and nodal (N) status were demonstrated. Low histological grade showed a strong association with a longer OS (P < 0.001). Correlation of survival and T status revealed a shorter OS in T3 tumors, but the results reached only marginal statistical significance (P = 0.070). In the multivariate Cox proportional hazards regression model, histological grade, T and N status remained valuable predictors of a worse survival with borderline significance for T [hazards ratio (HR) = 4.18 for G (if G = 3, P < 0.001); HR = 1.64 for T (if T = 3, P = 0.065); HR = 2.53 for N (if N = 1, P = 0.006)]. Higher grade, T or N status was associated with a worse OS. CONCLUSION: The immunohistochemically assessed level of COX-2 expression does not seem to represent a valuable independent prognostic factor and is not superior to the conventional prognostic factors.
Keywords: senioři; proporcionální rizikové modely; Proportional Hazards Models; regulace genové exprese enzymů; senioři nad 80 let; Prognosis; Pancreatic cancer; regulace genové exprese u nádorů; Pancreatic Ducts; imunohistochemie; monoklonální protilátky; Middle Aged; mužské pohlaví; Monoclonal antibody; nádory slinivky břišní; Cyclooxygenase-2; Antibodies, Monoclonal; Adult; Polyclonal antibody; Aged, 80 and over; Immunohistochemistry; ženské pohlaví; prognóza; Humans; Gene Expression Regulation, Neoplastic; Pancreatic Neoplasms; Gene Expression Regulation, Enzymologic; vývody pankreatu; lidé středního věku; Cyclooxygenase 2; cyklooxygenasa 2; dospělí; Female; Aged; lidé; Male